Overexpression of ABCC1 Confers Drug Resistance to Betulin - Chen, Xuan-Yu; Yang, Yuqi; Wang, Jing-Quan; Wu, Zhuo-Xun; Li, Jing; Chen, Zhe-Sheng (Frontiers in Oncology, 2021)
Betulin is a lupane-type pentacyclic triterpene, which is isolated from birch bark. It has a broad spectrum of biological and pharmacological properties, such as anti-inflammatory, anti-tumor, anti-viral, and anti-bacterial activity. Herein, we explored the factors that may result in betulin resistance, especially with respect to its interaction with ATP-binding cassette subfamily C member 1 (ABCC1). ABCC1 is an important member of the ATP-binding cassette (ABC) transporter family, which is central to mediating multidrug resistance (MDR) in naturally derived anticancer agents. An MTT-based cell viability assay showed that ABCC1 overexpression has the ability to desensitize both cancer cell line and gene-transfected cell line to betulin and that this betulin-induced resistance can be antagonized by a known ABCC1 inhibitor MK571 at 25 μM. Additionally, betulin upregulates the ABCC1 protein expression level in both concentration-dependent and time-dependent manners, also blocks the transport function mediated by ABCC1. Subsequently, a high affinity score of betulin was achieved in a computational docking analysis, demonstrating a strong interaction of betulin with ABCC1.